Penilaian Tingkat Kontribusi Teknologi Di PT. Wirasindo Santakarya Menggunakan Metode Teknomerik - Kristiawan, Nanang Arie; , Much. Djunaidi ST., MT; , Ir. Mila Faila Sufa, MT (2016)
The furniture industry today is an industry that can continue to grow in Indonesia. Economic activities that manage raw materials, semi-finished materials with a high value to users, including the design of an industry, the furniture industry in Indonesia is spread almost throughout the province, both in the island of Java and outside Java. Technology has an important influence in fostering excellence in competition among companies, Hence the method technometric is a method that can be used by the industry in determining the standard of its technology, in this study the level of technology in the review only of the four components of the technology are: technoware , humanware, infoware, organware. Based on the calculation of the contribution of technology components, obtained under technoware value of 0.314, humanware amounted to 0.387, infoware amounted to 0.668, and the value orgaware 0.75. The smallest contribution component is the technology component technoware. This is because the technology used is still manual and traditional. The contribution technoware intensity value is 0,199, the intensity contributions humanware is 0,384, the intensity contributions infoware is 0,299, and the intensity contributions orgaware is 0.116. The results of the research that has been conducted almost all production processes still use manual equipment, but nothing has been using technology to facilitate the production process, such as nail firing tools, welding tools and compressors, technometric obtained from the calculation that the TCC is 0.47233 so tesebut seemingly value indicates the level of technology that has been applied in the furniture industry PT. Wirasindo SANTAKARYA (WISANKA) is a semi-modern.